Hardcore smoking among daily smokers in male and female adults in 27 countries: a secondary data analysis of Global Adult Tobacco Surveys (2008-2014) - Chandrashekhar T Sreeramareddy; Joanne Hon; Anshad Mohamed Abdulla; Sam Harper (Journal of Global Health Reports)
# Background